Keputusan Pembelian Produk dengan Utilitarian Shopping Motivation, Hedonic Shopping Motivation dan Patronage Buying Motive Sebagai Variabel Dependent pada Konsumen Elzatta di Kabupaten Jombang - Abid Datul Mukhoyaroh; Rizka Kartika Dewi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2020)
Muslim fashion continues to develop over time, Muslim fashion is no longer just a desire that is expected to achieve a sense of satisfaction, but has become a necessity and has an impact on the growth of the Muslim fashion industry in Indonesia. One of them is the Elzatta gallery which is well known to most Indonesian people. This research aims to find out whether utilitarian shopping motivation (X1), hedonic shopping motivation (X2), and patronage buying motive (X3) influence purchasing decisions (Y). This research uses a quantitative approach with a survey method. The population in this study were consumers who had purchased Elzatta products in Jombang Regency with a sample of 100 people. Random sampling technique. The results of the calculated t test X1:0.002 X2:0.003 The coefficient of determination data shows a value of 0.779, meaning that 77.9% of consumer purchasing decisions for Elzatta products in Jombang Regency are influenced by these three factors, while 22.1% are influenced by other variables outside this research.